Analisis Cost Volume Profit (CVP) sebagai Metode Manajemen Laba pada UMKM Madu Asy-Syifa - Rahmat Hidayat (Yayasan Literasi Sains Indonesia, 2024)
Micro Small and Medium Enterprises (MSMEs) are a driving force in the country's economy but often face obstacles in maxi mizing profits. Profit management requires calculations using Cost Volume Profit (CVP) analysis. MSMEs Madu Asy-Syifa has never used Cost Volume Profit analysis calculations so they have not been able to optimize profits. This study aims to analyze CVP calculations as a method for profit management in MSMEs Madu Asy-Syifa The research method used is descriptive qualitative, focusing on observation and interview approaches. Based on the calculation of CVP analysis, MSMEs Madu Asy-Syifa must be able to sell 570 units of honey products with sales details of 105 units of large-size products, 127 units of medium-sized products, and 338 units of small-sized products and be able to make sales and earn income of Rp65,850,000 for one year in order to reach the Break Even Point condition, obtain a 53.6% Contribution Margin Ratio, the maximum decrease in Margin of safety in rupiah of Rp245,425,000,-, and Degree of Operating Leverage of 1.27 times of Net Income. Based on the study, the author recommends that MSMEs Madu Asy-Syifa consistently utilize Cost Volume Profit analysis calculations to manage profits effectively.